Biglycan promotes hepatic fibrosis through activating heat shock protein 47. (21st November 2022) - Yu, Mengli; He, Xinjue; Song, Xin; Gao, Jianguo; Pan, Jiaqi; Zhou, Tianyu; Wang, Qinqiu; Zhu, Wei; Ma, Huijian; Zeng, Hang; Xu, Chengfu; Yu, Chaohui
Abstract: Background: Biglycan (BGN) is a small leucine‐rich proteoglycan that participates in the production of excess extracellular matrix (ECM) and is related to fibrosis in many organs. However, the role of BGN in liver fibrosis remains poorly understood. This study aimed to investigate the role and mechanism of BGN in liver fibrosis. Methods: Human liver samples, Bgn −/0 (BGN KO) mice and a human LX‐2 hepatic stellate cells (HSCs) model were applied for the study of experimental fibrosis. GEO data and single‐cell RNA‐seq data of human liver tissue were analysed as a bioinformatic approach. Coimmunoprecipitation, immunofluorescence staining, western blotting and qRT–PCR were conducted to identify the regulatory effects of BGN on heat shock protein 47 (HSP47) expression and liver fibrosis. Results: We observed that hepatic BGN expression was significantly increased in patients with fibrosis and in a mouse model of liver fibrosis. Genetic deletion of BGN disrupted TGF‐β1 pathway signalling and alleviated liver fibrosis in mice administered carbon tetrachloride (CCl4 ). siRNA‐mediated knockdown of BGN significantly reduced TGF‐β1‐induced ECM deposition and fibroblastic activation in LX‐2 cells. Mechanistically, BGN directly interacted with and positively regulated the collagen synthesis chaperon protein HSP47. Rescue experiments showed that BGN promoted hepatic fibrosis by regulating ECM deposition and HSC activation by positively regulating HSP47. Conclusion: Our data indicate that BGN promotes hepatic fibrosis by regulating ECM deposition and HSC activation through an HSP47‐dependent mechanism. BGN may be a new biomarker of hepatic fibrosis and a novel target for disease prevention and treatment.